Retraction: Sublimable cationic Ir(iii) phosphor using chlorine as a counterion for high-performance monochromatic and white OLEDs. Issue 10 (21st January 2020) - Ding, Lei; Zang, Chun-Xiu; Mao, Hui-Ting; Shan, Guo-Gang; Wen, Li-Li; Sun, Hai-Zhu; Xie, Wen-Fa; Su, Zhong-Min
Abstract : Retraction of 'Sublimable cationic Ir(iii ) phosphor using chlorine as a counterion for high-performance monochromatic and white OLEDs' by Lei Ding et al., Chem. Commun., 2018, 54, 11761–11764.